Constructing the 'citizen' in citizenship education - Maryam Nabavi (Canadian Society for Studies in Education, 2010)
In the field of education, the discourses of 'citizenship education' aremore than at any other period of Canadian historycentre stage. As public schooling strives to offer citizenship education amenable to the needs of varied identities, the ideological premises, concepts, and goals of citizenship education must be interrogated. Critically synthesizing the developments of citizenship education since the Multiculturalism Policy of 1971, the gaps in citizenship education will be explored by discussing policy and pedagogical approaches. This article will conclude by offering pedagogical and conceptual alternatives to citizenship education, which can serve to address the outlined gaps in learning for citizenship for diverse learners.